2012
DOI: 10.1152/ajpcell.00237.2012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nonselective cation channel in isolated lens fiber cells that is activated by cell shrinkage

Abstract: The initiation of lens cataract has long been associated with the development of a membrane "leak" in lens fiber cells that depolarizes the lens intracellular potential and elevates intracellular Na(+) and Ca(2+) concentrations. It has been proposed that the leak observed in cataractous lenses is due to the activation of a nonselective cation (NSC) conductance in the normal electrically tight fiber cells. Studies of the membrane properties of isolated fiber cells using the patch-clamp technique have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…It has been hypothesized that Panx1 forms the probenecid-inhibitable channels that release ATP from lens epithelial cells after exposure to hyposmotic stress (Shahidullah et al, 2011, 2012). Gunning et al (2012) have found that lens fiber cells contain a non-specific cation conductance that may be distinct from connexin hemichannels. It is stimulated by hypertonic stress or isosmotic cell shrinkage and may be involved in volume regulation.…”
Section: Other Lens Channels That Resemble Connexin Hemichannelsmentioning
confidence: 99%
“…It has been hypothesized that Panx1 forms the probenecid-inhibitable channels that release ATP from lens epithelial cells after exposure to hyposmotic stress (Shahidullah et al, 2011, 2012). Gunning et al (2012) have found that lens fiber cells contain a non-specific cation conductance that may be distinct from connexin hemichannels. It is stimulated by hypertonic stress or isosmotic cell shrinkage and may be involved in volume regulation.…”
Section: Other Lens Channels That Resemble Connexin Hemichannelsmentioning
confidence: 99%